INNOVATIVE THINKING AND SOCIAL ACTIVITY IN YOUTH: AN INTEGRATIVE APPROACH - Utaev Gayrat Gaybullaevich (Web of Journals Publishing, 2025)
This article addresses the issues of raising the future generation of our country, training them as well-rounded, humane, and responsible individuals towards society and nature, as well as increasing the activity of highly spiritual youth in the social and political spheres of our country.
Keywords: New Uzbekistan, Third Renaissance, development, strong civil society, spirituality, culture, advancement, youth, tasks, innovative thinking, loyalty to national ideology, spiritual and educational advocacy, advocacy mechanisms, youth policy, improving legal culture of youth, national education system, modern technologies.